Proses Pengembangan Media Pembelajaran Konten Pasar Tradisional Berbasis VR - Pratama, Yogie; Fiantika, Feny Rita; Prayogo, Prayogo (Program Studi Pendidikan Matematika, Universitas Majalengka, 2025)
Traditional markets are closely related to mathematics learning, as they provide a relevant environment for applying various mathematical concepts in a practical manner. In the field of education, various technology-based learning media have been developed, one of which is Virtual Reality (VR). This study aims to enhance students' interest in learning through Virtual Reality-based learning media featuring traditional market content applied in mathematics instruction. This research follows a Research and Development (RnD) approach using the 4D development model, which consists of four main stages: 1) Define, 2) Design, 3) Develop, and 4) Disseminate. During the development process, the researchers utilized expert validation instruments and student questionnaires. The study population consisted of fifth-grade students at SDN Kebonagung I Sukodono, Sidoarjo, with a research sample of three students. The findings indicate that media validation by experts was categorized as